Comprehending the Cost - Z. W. Taylor (Journal of College Orientation, Transition, and Retention, 2019)
As the cost of college rises, students and their families seek new ways to save money. Application fee waivers are offered by many postsecondary institutions in the United States, but higher education as a field has not examined whether or not the application fee waiver statement published on each institution’s website is readable. This study examined the readability of application fee waiver statements of the public and private institutions charging the highest undergraduate application fees for the 2015-2016 academic year (n = 39). The results suggest that the majority of application fee waiver statements are unreadable by prospective postsecondary students, and no statements were translated into a language other than English. Implications for policy, practice, and future research are addressed.